Abnormalities in functional connectivity in borderline personality disorder: Correlations with metacognition and emotion dysregulation. (30th January 2019) - Quattrini, Giulia; Pini, Lorenzo; Pievani, Michela; Magni, Laura R; Lanfredi, Mariangela; Ferrari, Clarissa; Boccardi, Marina; Bignotti, Stefano; Magnaldi, Silvia; Cobelli, Milena; Rillosi, Luciana; Beneduce, Rossella; et al.
Highlights: BPD patients showed altered functional connectivity at rest. Lower functional connectivity emerged in the DMN, SN, and ECN. DMN connectivity was correlated with anger. SN connectivity was correlated with metacognitive abilities. Abstract: A few studies reported functional abnormalities at rest in borderline personality disorder (BPD), but their relationship with clinical aspect is unclear. We aimed to assess functional connectivity (FC) in BPD patients and its association with BPD clinical features. Twenty-one BPD patients and 14 healthy controls (HC) underwent a multidimensional assessment and resting-state fMRI. Independent component analysis was performed to identify three resting-state networks: default mode network (DMN), salience network (SN), and executive control network (ECN). FC differences between BPD and HC were assessed with voxel-wise two-sample t -tests. Additionally, we investigated the mean FC within each network and the relationship between connectivity measures and BPD clinical features. Patients showed significant lower mean FC in the DMN and SN, while, at the local level, a cluster of lower functional connectivity emerged in the posterior cingulate cortex of the DMN. The DMN connectivity was positively correlated with the anger-state intensity and expression, while the SN connectivity was positively correlated with metacognitive abilities and a negative correlation emerged with the interpersonal aggression. The dysfunctional connectivity within these networks might explain clinical features of BPD patients.